Porphyromonas Gingivalis Response to Ultrasonication - Kamineni, Srinath; Dhawan Vikas; Huang, Chifu (International Journal of Clinical Microbiology, 2019)
Introduction Ultrasound technology has previously been applied for cataract removal and tennis elbow treatment. Recent data supports the use of ultrasonic debridement in the treatment of diabetic foot ulcers. No data is available concerning the potential antibacterial properties of a clinical grade, lower energy ultrasound probe. We investigated the effect of a ultrasonic probe with respect to P gingivalis bacterial viability. Methods A Tenex Tx1 probe with standard settings for clinical use was used for this study. A Gram negative (Porphyromonasgingivalis) bacteria, known for its pathological activity, was investigated. The bacteria was cultured in an anaerobic broth, re-suspended to achieve a consistent bacterial count, and 5ml of this re-suspension was placed in a test tube for testing. Each tube was sonicated with the Tx1 probe for varying lengths of time (10, 30, 60, 120 seconds). The sonicated was diluted and plated on blood-agar plates, followed by incubation for 48 hours at 37°C in an anaerobic growth chamber. The number of colony forming units were counted, on each plate and the anti-bacterial effect was calculated. A one way analysis of variance was performed for statistical analysis. Results A significant time-dependent antibacterial effect was demonstrated with sonication. When comparing the kill rate between the control and 120 seconds of sonication P Gingivalis had a 64% kill rate. This was the only statistically significant time comparison achieved, although the trend for all the time intervals was a reduction in the colony forming unit counts. Conclusion This study demonstrates that a clinically available ultrasonic probe (Tenex Tx1) has an antibacterial effect against the gram negative anaerobic bacterial species P gingivalis. Complete deactivation was not achieved, and there was a variation in effect dependent on the time of active sonication, with greater sonication times leading to greater kill rates. This data may partially help to explain the ability for ultrasonic debridement to result in the healing of long standing diabetic ulcers, that have been recalcitrant to other forms of treatment.
Keywords: Porphyromonas Gingivalis